Utilising public health flexibilities in the era of COVID-19: An analysis of intellectual property regulation in the OAPI and MENA regions - Yousuf A. Vawda; Bonginkosi Shozi (South Centre, 2021)
The paper explores the unique approaches to IP protection in the countries belonging to the Organisation Africaine de la Propriété Intellectuelle/African Intellectual Property Organization (OAPI) and the Middle East and North Africa (MENA) regions; the limited extent to which legal and policy frameworks with regard to TRIPS flexibilities have been adopted and implemented in pursuit of access to medicines in those countries; and makes recommendations in order to optimise the use of the flexibilities in advancing public health objectives. In the context of the COVID-19 pandemic, the impact of IP rights on access, and some approaches to countering the challenges to access are also discussed.
Keywords: 300; Immaterialgüterrechte; Patentrecht; Arzneimittel; Impfung; Preis; Preisregulierung; Coronavirus; MENA-Staaten; Afrika